2018
DOI: 10.1096/fj.201800597r
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from high‐glucose‐stimulated Schwann cells promote development of diabetic peripheral neuropathy

Abstract: Schwann cells actively interact with axons of dorsal root ganglia (DRG) neurons. Exosomes mediate intercellular communication by transferring their biomaterials, including microRNAs (miRs) into recipient cells. We hypothesized that exosomes derived from Schwann cells stimulated by high glucose (HG) exosomes accelerate development of diabetic peripheral neuropathy and that exosomal cargo miRs contribute to this process. We found that HG exosomes contained high levels of miR-28, -31a, and -130a compared to exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 104 publications
4
54
0
Order By: Relevance
“…Exosomes can be produced by the vast majority of cells with different origins and numerous functions. The cells from which exosomes are secreted include T cells [73,74], platelets [75], megakaryocytes [76] mast cells [77,78], neurons [79,80], oligodendrocytes [81] and Schwann cells [82][83][84][85]. Similarly, cells with stemness properties, such as mesenchymal stromal cells (MSCs) [86][87][88] and induced pluripotent stem cells (iPSCs) [89,90], have been reported to release exosomes.…”
Section: Different Types and Functions Of Cells That Release Exosomesmentioning
confidence: 99%
“…Exosomes can be produced by the vast majority of cells with different origins and numerous functions. The cells from which exosomes are secreted include T cells [73,74], platelets [75], megakaryocytes [76] mast cells [77,78], neurons [79,80], oligodendrocytes [81] and Schwann cells [82][83][84][85]. Similarly, cells with stemness properties, such as mesenchymal stromal cells (MSCs) [86][87][88] and induced pluripotent stem cells (iPSCs) [89,90], have been reported to release exosomes.…”
Section: Different Types and Functions Of Cells That Release Exosomesmentioning
confidence: 99%
“…Our group showed that exosomes derived from Schwann cells (SC-exos) increased intraepidermal nerve fiber density in the footpad and reduced axonal and myelin damage of the sciatic nerve, leading to a reduction of neuropathic symptoms in DN mice (124). In contrast, exosomes derived from Schwann cells cultured in highglucose medium facilitated the development of DN by reducing epidermal nerve fibers (125). Naïve SC-exos were enriched in miR-21, miR-27a, and miR-146a.…”
Section: Extracellular Mirnas In Peripheral Neurovascular Functionmentioning
confidence: 99%
“…Bioinformatics analysis revealed that miR-21, miR-27a, and miR-146a target Semaphorin 6A (SEMA6A), Ras homolog gene family, member A (RhoA), phosphatase and tensin homolog (PTEN), and nuclear factor-κB (NF-κB) genes, respectively, thereby protecting axons and improving axonal growth. Exosomes isolated from Schwann cells stimulated by high glucose were enriched for miR-28, miR-31a, and miR-130, which target DNA methyltransferase-3a (NDNMT3A), NUMB (endocytic adaptor protein), synaptosome associated protein 25 (SNAP25), and growth-associated protein-43 (GAP43), separately and participate in axonal growth (125).…”
Section: Extracellular Mirnas In Peripheral Neurovascular Functionmentioning
confidence: 99%
“…Accumulating evidence revealed that Schwann cell, as the main cell of peripheral nerve, suffered from dysfunction during the occurrence and development of DPN, including cell apoptosis (Zhu et al, 2018), abnormal autophagy (Du et al, 2019) and dedifferentiation (Hao et al, 2015). Hyperglycemia and the related derivatives such as methylglyoxal and advanced glycation end products were the main pathogenic factors to result in Schwann cell dysfunction (Jia et al, 2018; Xu et al, 2019). However, many patients with blood glucose controlled well were also subjected to the preventable pathogenesis of DPN.…”
Section: Introductionmentioning
confidence: 99%
“…products were the main pathogenic factors to result in Schwann cell dysfunction (Jia et al, 2018;Xu et al, 2019). However, many patients with blood glucose controlled well were also subjected to the preventable pathogenesis of DPN.…”
mentioning
confidence: 99%